The effect of eccentric exercise on skeletal muscle release of novel molecules (myokines) in healthy young individuals - Parmar, Biraj (2017)
The aim of this thesis was to test the hypothesis that maximal eccentric contractions would augment the release of novel myokines (including Fibroblast Growth Factor-21) from muscle tissue into systemic circulation due to the greater structural damage and increased inflammatory response normally associated with eccentric exercise. Furthermore, for the first time the active form of FGF-21 was measured in circulation in response to exercise in healthy humans. Nine physically active young healthy males (age 25 ± 3.8 years, height 177.5 ± 7.24 cm, body mass 73.3 ± 11.8 kg, body mass index (BMI) 23.1 ± 2.78 kg/m2) at baseline completed a series of functional tests to access maximal isometric strength and maximal isokinetic strength. All subjects then completed 3 sets of single-leg maximal eccentric contractions using their non-dominant leg, whilst the dominant leg served as a control. Each of the 3 sets consisted of 25 repetitions with a 5-minute rest period between each set. Subjects thereafter rested in a semi-supine position for 3-hours. Forty-eight hours after the end of the last set of maximal eccentric contractions, subjects returned to the lab and conducted the same muscle function tests. Prior to exercise, an intravenous cannula was inserted retrograde into the superficial hand vein of one arm for arterialised-venous blood sampling for the determination of glucose, lactate, total FGF-21, active FGF-21 and Fibroblast activation protein (FAP). Two further cannulas were inserted into the common femoral vein of the exercised leg and the control leg for deep venous blood sampling. Blood samples from each sampling line were obtained before and after each exercise bout and at regular intervals (every 20 minutes) during the 3-hour recovery period. Blood flow of the superficial femoral artery using Doppler ultrasound was also measured at the same time intervals. Muscle biopsy samples from the vastus lateralis were also taken at baseline (exercise and control legs), immediately post-exercise (exercise leg only), after 3-hours of recovery (exercise leg only) and 48-hours after exercise (exercise and control legs) for the determination of FGF-21 protein content. The main findings from this study showed there was no significant increase in total or active FGF-21 secreted from skeletal muscle into the systemic circulation in response to exercise. Furthermore, skeletal muscle FGF-21 protein content showed no changes in response to eccentric contractions. However, there was a significant increase in arterialised and venous FAP concentrations, an enzyme that cleaves and inactivates FGF-21 during exercise, which may suggest that the release of FAP may occur via other tissues. In conclusion, the present study shows that single leg maximal eccentric contractions do not augment the release of total or active FGF-21 from skeletal muscle into systemic circulation in humans. It also raises a novel interesting possibility that FAP released into systemic circulation may play a role in the inactivation of FGF-21 during exercise.